Brazilian experience in EU-CORE: daptomycin registry and treatment of serious Gram-positive infections - Timerman,Artur (2013)
OBJECTIVES: To collect data about non-controlled prescribing use of daptomycin and its impact among Brazilian patients with serious Gram positive bacterial infection, as well as the efficacy and safety outcomes. MATERIALS AND METHODS: This is a multi-center, retrospective, non-interventional registry (August 01, 2009 to June 30, 2011) to collect data on 120 patients (44 patients in the first year and 76 patients in the second year) who had received at least one dose of commercial daptomycin in Brazil for the treatment of serious Gram-positive bacterial infection. RESULTS: Right-sided endocarditis (15.8%), complicated skin and soft tissue infections (cSSTI)wound (15.0%) and bacteremia-catheter-related (14.2%) were the most frequent primary infections; lung (21.7%) was the most common site for infection. Daptomycin was used empirically in 76 (63.3%) patients, and methicillin-resistant Staphylococcus aureus (MRSA) was the most common suspected pathogen (86.1%). 82.5% of the cultures were obtained prior to or shortly after initiation of daptomycin therapy. Staphylococcus spp. - coagulase negative, MRSA, and methicillin-susceptible S. aureus were the most frequently identified pathogens (23.8%, 23.8% and 12.5%, respectively). The most common daptomycin dose administered for bacteremia and cSSTI was 6 mg/kg (30.6%) and 4 mg/kg (51.7%), respectively. The median duration of inpatient daptomycin therapy was 14 days. Most patients (57.1%) did not receive daptomycin while in intensive care unit. Carbapenem (22.5%) was the most commonly used antibiotic concomitantly. The patients showed clinical improvement after two days (median) following the start of daptomycin therapy. The clinical success rate was 80.8% and the overall rate of treatment failure was 10.8%. The main reasons for daptomycin discontinuation were successful end of therapy (75.8%), switched therapy (11.7%), and treatment failure (4.2%). Daptomycin demonstrated a favorable safety and tolerability profile regardless of treatment duration. CONCLUSIONS: Daptomycin had a relevant role in the treatment of Gram-positive infections in the clinical practice setting in Brazil.